Re‐hospitalization after pediatric kidney transplant: A single‐center study. (24th May 2020) - Verghese, Priya S.; Chinnakotla, Srinath; Berglund, Danielle; Matas, Arthur J.; Chavers, Blanche
Abstract: Background: Little data exist on re‐hospitalization rates in pediatric kidney recipients (KTx) particularly with the evolution of transplant immunosuppression. Methods: In a single‐center, retrospective study of pediatric KTx between 2006 and 2016, we assessed re‐hospitalization after KTx admission, stratified by whether the re‐admit was early (<30 days post‐KTx discharge) or late (>30 days), and compared two different immunosuppression eras (one with and one without steroids). Results: Of 197 KTx, 156 (79%) patients were re‐hospitalized in 1st year, 85 (56%) within 30 days of discharge (total 490 1st year re‐hospitalizations). Younger age was associated with early and late re‐hospitalizations. African American race was associated with early re‐hospitalizations. Of the 123 and 74 discharged on steroid‐avoidance (maintenance immunosuppression included MMF in 95%; FK in 50%; CSA in 50%) and steroid‐inclusive (AZA in 66%; MMF in 34%; FK in 30%; CSA in 70%), re‐hospitalization rates, timing post‐transplant, length, and number were not significantly different ( P .38; .1; .56; .11). Admission diagnoses analysis demonstrated that steroid‐avoidance recipients had anemia/leucopenia/thrombocytopenia, significantly more often, as one of their admission diagnoses (16% vs 4%; P < .001) and had a rejection diagnosis significantly less often (6% vs 18%; P < .001). Infection diagnoses were not statistically different between groups. Re‐hospitalization, early or late, did not predict worse graft/ patient survival but predicted further hospitalizations. Conclusions: Re‐hospitalization is common after pediatric transplant discharge and predicts further hospitalization regardless of discharge on or off steroids.